INFLUENCE OF A COMPOSITION BASED ON MICROORGANISMS ON WHEAT AND POTATO PRODUCTS - Khujanazarova Mutabar Kushokovna; Khalmuminova Gulchehra Kulmuminovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, wheat is one of the important crops grown in our republic. It is no secret that the insufficient introduction of crop rotation systems leads to a sharp decrease in soil fertility, which, in turn, leads to a decrease in productivity and, as a result, to excessive costs for growing plants, and in areas of secondary salinization on irrigated lands of our republic, fallow that in order to increase the efficiency of high yields of sweet potatoes and potatoes, including the creation of new competitive microbial preparations that increase salt tolerance through biotechnological and innovative methods and assess their practical value.